Forest reorganisation effects on fuel moisture content can exceed changes due to climate warming in wet temperate forests - Tegan P. Brown; Thomas J. Duff; Assaf Inbar; Patrick N. J. Lane; Gary J. Sheridan (Global Change Biology, 2024)
The distributions of vegetation and fire activity are changing rapidly in response to climate warming. In many regions, climate effects on dead fuel moisture content (FMC) are expected to increase future wildfire activity. However, forest FMC is largely driven by microclimate conditions, which are moderated from open weather by vegetation canopies. As shifts in vegetation increase under climate warming, the extent to which future fire activity will be driven by climate directly or associated vegetation shifts remains unresolved. Here, we present a study aimed at quantifying the relative magnitudes of (i) direct climate warming, and (ii) vegetation change, on FMC. Field sites to evaluate these effects were established in a natural laboratory of altered forest states to mature wet temperate forest in south‐eastern Australia. FMC was estimated using a process‐based model and 48 years of reconstructed climate data. Canopy effects on microclimate were captured by transferring inputs from climate to microclimate using models parameterised with field observations. To evaluate the relative magnitude of climate and vegetation effects, we calculated the maximum difference in mean annual FMC across annual climate replicates and compared this to FMC differences across reorganising forest sites. Our results show vegetation effects on FMC can exceed those related to expected climate change. Changes to forest structure and composition increased (+15.7%) and decreased (−12.3%) mean annual FMC, with a larger negative effect when forest cover was completely removed (−18.5%). In contrast, the largest climate effect on FMC was −6.6% across 48‐years of data. Our study demonstrates that the magnitude of vegetation effects on FMC can exceed expected climate change effects. Models of future fire activity that do not account for changing vegetation effects on microclimate are omitting a key biophysical control on FMC and therefore may not be accurately predicting future fire activity.

Critical climate thresholds for fire in wet, temperate forests - Richard G. Benyon; Assaf Inbar; Gary J. Sheridan; Patrick N.J. Lane (Forest Ecology and Management, 2023)

Variable self-thinning explains hydrological responses to stand replacement in even-aged forests - Richard G. Benyon; Assaf Inbar; Gary J. Sheridan; Christopher S. Lyell; Patrick N.J. Lane (Journal of Hydrology, 2023)